Influence of Human Resource Empowerment on Organizational Performance of Selected Public University Campuses in Western Kenya - Osuwo, Charity Achola (JOOUST, 2017)
Human resource empowerment is a process of supporting the necessary capacities in employees to motivate them to increase value in their organizations. This includes optimizing responsibilities in the organization, through efficiency and effectiveness. This study aimed at establishing whether selected public campuses in Western Kenya have adequately empowered their human resources with the view of achieving improved organizational performance. The study was guided by three objectives; to establish the influence of access to professional development, access to organizational resources and rewarding system on organizational performance. Structural empowerment theory was the guiding theory. The study employed correlational research design and the target population was 3857. Stratified random and purposive sampling methods were used to get samples from the various levels of sampling and from the subgroups within the population to arrive at a study sample of 362. Research instruments were questionnaires and interview schedules. Validity was ascertained by expert judgment from the school of Business and Economics. To ensure reliability of the instruments, the researcher carried out a pilot study and employed a test-retest technique to help identify areas of weakness for modification. Reliability coefficient was calculated by use of Cronbach's alpha formula and a value of 0.82 was obtained. Quantitative data was analyzed using descriptive statistics and inferential statistics. Content analysis was used to analyze qualitative data which was then sorted into themes. Karl Pearson's coefficient of correlation was used to establish the relationships between the variables of the study and the correlation coefficient between professional development and organizational performance was r=0.509, access to organizational resources and organizational performance was r=0.522 while that of rewarding system and organizational performance was r=0.459. A positive significant relationship between Human resource empowerment and Organizational performance with a correlation coefficient of r=0.556 between them was established. Regression analysis indicated that all the independent variables significantly influenced organizational performance which was the dependent variable. Both stepwise regression model and ANOVA show that there is a significant relationship between organizational performance and human resource empowerment. The importance of the study is that it presents an overview on the influence of human resource empowerment on organizational performance. The study concludes that the institutions have recognized the importance of human resource empowerment and recommended that they only need to embed and implement these processes in equitable, accessible and desirable manner to employees